Trinidad B.W.I. - (:unkn) unknown (My University, 2008)
Photograph of a Creole vendor carrying a basket containing her wares on her head.
Colour:Black and White ; Style:Portrait ; Other:Bordered, Divided
Keywords: Postcards; Street vendors